2022
DOI: 10.1371/journal.pone.0268084
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards COVID-19 among secondary school students in Gondar town, Northwest Ethiopia

Abstract: Background In Ethiopia, an array of measures have been adopted to control the rapid spread of the Coronavirus Disease 2019 (COVID-19) pandemic. Such control measures could significantly influence the knowledge, attitudes, and practices (KAP) towards COVID-19 in the general population. However, still, there is scarce information regarding the KAP of students towards the COVID-19 pandemic. Therefore, this study aimed to assess KAP and associated factors towards COVID-19 among secondary school students in Gondar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Conversely, a study in the Kingdom of Bhutan among college students found good knowledge that translated into good practices toward COVID-19 (85). Similarly, a recent study in Ethiopia reported good knowledge and good practices regarding COVID-19 (86). The good knowledge and practices reported in other studies could be due to the increased dissemination of educational information regarding COVID-19 by the governments and related stakeholders.…”
Section: Discussionmentioning
confidence: 83%
“…Conversely, a study in the Kingdom of Bhutan among college students found good knowledge that translated into good practices toward COVID-19 (85). Similarly, a recent study in Ethiopia reported good knowledge and good practices regarding COVID-19 (86). The good knowledge and practices reported in other studies could be due to the increased dissemination of educational information regarding COVID-19 by the governments and related stakeholders.…”
Section: Discussionmentioning
confidence: 83%
“…One of severe outcomes of the COVID-19 is that it can cause a fatal effect on humans after its short time of detection [2]. It mainly spread through respiratory droplets [4]. So, the people got infected when they come in contact with infected patients' saliva and nose discharges [4].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly spread through respiratory droplets [4]. So, the people got infected when they come in contact with infected patients' saliva and nose discharges [4]. Studies demonstrated that approximately 31% of patients infected with SARS-CoV-2 was asymptomatic while 40% of symptomatic patients had mild or moderate symptoms including fever, dry cough, myalgia, tiredness [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social media platform has significantly contributed to the spread of information and has praised Chinese institutions for its ongoing COVID-19 alerts that enabled students to have a complete understanding ( 22 ). Since the media and other related parties play a significant role in the acceptance or otherwise of the vaccine, the governments have advised them to spread accurate, reliable, and consistent COVID-19 vaccine information to foster public trust ( 23 ).…”
Section: Introductionmentioning
confidence: 99%